2018
DOI: 10.1038/s41598-018-22054-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Injectable Slow-Release Metformin Formulation and Evaluation of Its Potential Antitumor Effects

Abstract: Metformin is an antidiabetic drug which possesses antiproliferative activity in cancer cells when administered at high doses, due to its unfavorable pharmacokinetics. The aim of this work was to develop a pharmacological tool for the release of metformin in proximity of the tumor, allowing high local concentrations, and to demonstrate the in vivo antitumor efficacy after a prolonged metformin exposition. A 1.2% w/w metformin thermoresponsive parenteral formulation based on poloxamers P407 and P124, injectable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Starting from epidemiologic studies, a potential chemopreventive effect of metformin was identified in diabetic patients, demonstrating a significant lower incidence of several solid tumors ( Evans et al, 2005 ). Following this evidence, numerous preclinical studies demonstrated that metformin significantly reduce cell proliferation in different in vitro and in vivo cancer models, including breast ( Hirsch et al, 2009 ; Barbieri et al, 2015 ; Baldassari et al, 2018 ), prostate ( Ben Sahra et al, 2011 ; Kato et al, 2015 ), colon ( Zaafar et al, 2014 ), neuroblastoma ( Costa et al, 2014 ), osteosarcoma ( Gatti et al, 2016 , 2018 ; Xu et al, 2017 ; Paiva-Oliveira et al, 2018 ), and, relevant to this study, GBM ( Sato et al, 2012 ; Wurth et al, 2013 ; Yang et al, 2016 ; Kim et al, 2017 ). Notably, while displaying toxic effects in several tumor cells, metformin is basically harmless for normal stem cells ( Wurth et al, 2013 ; Gritti et al, 2014 ), confirming the safety profile of this drug as observed after chronic use in diabetic patients.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Starting from epidemiologic studies, a potential chemopreventive effect of metformin was identified in diabetic patients, demonstrating a significant lower incidence of several solid tumors ( Evans et al, 2005 ). Following this evidence, numerous preclinical studies demonstrated that metformin significantly reduce cell proliferation in different in vitro and in vivo cancer models, including breast ( Hirsch et al, 2009 ; Barbieri et al, 2015 ; Baldassari et al, 2018 ), prostate ( Ben Sahra et al, 2011 ; Kato et al, 2015 ), colon ( Zaafar et al, 2014 ), neuroblastoma ( Costa et al, 2014 ), osteosarcoma ( Gatti et al, 2016 , 2018 ; Xu et al, 2017 ; Paiva-Oliveira et al, 2018 ), and, relevant to this study, GBM ( Sato et al, 2012 ; Wurth et al, 2013 ; Yang et al, 2016 ; Kim et al, 2017 ). Notably, while displaying toxic effects in several tumor cells, metformin is basically harmless for normal stem cells ( Wurth et al, 2013 ; Gritti et al, 2014 ), confirming the safety profile of this drug as observed after chronic use in diabetic patients.…”
Section: Introductionmentioning
confidence: 61%
“…However, important issues and concerns about this off-label activity are still unsolved. In particular, extremely high drug concentrations (within the mM range) are required to induce antitumor effects in in vitro studies, although in vivo metformin intratumoral concentrations were reported to be several fold higher than in plasma ( Nguyen et al, 2017 ; Baldassari et al, 2018 ). It was therefore proposed that protracted in vivo treatment using clinically reachable doses, can possibly induce antitumor effects ( Gritti et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most relevant information that can be obtained by identification of CSC from different tumors, is the possibility to analyze, with good translational potential, the sensitivity of this subpopulation to traditional or innovative pharmacological treatments. For example, studies on CSC from glioblastoma, breast cancer or osteosarcoma (119,(121)(122)(123), demonstrated a higher sensitivity of this subpopulation to metformin, as compared to "differentiated" tumor cells, determining the development of a drug repositioning approach (124,125). In particular, while it is well-accepted that stem-like cells are particularly resistant to classical cytotoxic drugs due to the overexpression of drug-extruding pumps and DNA-repairing enzymes (110), in CSC cultures from different tumors the sensitivity to molecular-targeted drugs, in particular to tyrosine kinase inhibitors, is retained (114,126).…”
Section: Drug Sensitivity Of Pituitary Adenoma Stem Cellsmentioning
confidence: 99%
“…thermo-responsive polymer is mixed with the API at room temperature for subsequent injection into the body. After that, the body's temperature increase above polymer LCST induces a phase transition that forms a physical gel, favoring the release of the drug from the scaffold [141][142][143].…”
Section: Drug Delivery Applications In Wound Healingmentioning
confidence: 99%